Magic and irrationality in management : the case of fads - Trepo, Georges (Revista de Ciencias de la Administración, 2004)
Management tools are being launched by consultants with the help of academics and the media/press, at an ever faster pace. Managers wonder whether they should follow or avoid fads : what will be left over in every day’s practice, when the “mediatic frenzy” is gone, they ask ? After observing hundreds of companies over 35 years, we offer some insights on this topic.